Numerical Simulation of Shaking Table Tests on Full-Scale Stone Masonry Buildings. Issue 2 (2nd April 2016) - Penna, Andrea; Senaldi, Ilaria; Galasco, Alessandro; Magenes, Guido
ABSTRACT: Based on the outcomes of a recent experimental project addressing unreinforced stone masonry undertaken at the European Centre for Training and Research in Earthquake Engineering, the seismic response exhibited by two full-scale building prototypes during shaking table tests was simulated according to an existing equivalent frame modeling approach involving nonlinear macroelements. Given the use of different strengthening solutions, the two building specimens strongly differed in the in-plane stiffness of their timber floors and roof diaphragms. This article addresses several issues concerning numerical modeling of the seismic response of this type of masonry construction, particularly its effect upon assessing the global response of the discretization and geometry of the equivalent frame model and upon definition of model parameters based on tests of material characteristics and lateral response of structural members. Even in the case of flexible diaphragms, the results of pushover analysis of the calibrated models provided a fair approximation in terms of both envelope curve and damage pattern. The results of time history analysis accounting for cumulative damage indicate good simulation in terms of hysteretic response as well.